RV Function by cardiac magnetic resonance and its relationship to RV longitudinal strain and neutrophil/lymphocyte ratio in patients with acute inferior ST-segment elevation myocardial infarction undergoing primary percutaneous intervention - Taha, Salma; Ali, Shrouk Kelany; D’Ascenzo, Fabrizio; Hasan-Ali, Hosam; Ghzally, Yousra; Ghany, Mohamed Abdel (Journal of Cardiology and Cardiovascular Medicine, 2021)
Background: Although acute inferior myocardial infarction (MI) is usually regarded as being lower risk compared with acute anterior MI, right ventricular (RV) myocardial involvement (RVMI) may show an increased risk of cardiovascular (CV) morbidity and mortality in patients with inferior MI. CMR is ideal for assessing the RV because it allows comprehensive evaluation of cardiovascular morphology and physiology without most limitations that hinder alternative imaging modalities. Objectives: To evaluate the sensitivity of strain and strain rate of the RV using 2D speckle tracking echo and the neutrophil/ lymphocyte ratio (NLR) compared to cardiac MRI (CMR) as the gold standard among patients with inferior STEMI undergoing primary percutaneous coronary intervention (PCI). Methodology: 40 Patients with inferior MI who had primary PCI were included in the study; they were divided into two groups according to the RVEF using CMR. NLR was done in comparison to RVEF. Results: out of the 40 patients, 18 (45%) patients had RV dysfunction. 2D echocardiography was done for all patients, where fractional area change (FAC) in the RV dysfunction group appeared to be significantly reduced compared to the group without RV dysfunction (p value = 0.03). In addition, RV longitudinal strain (LS) by speckle tracking echo was reduced with an average of 19.5 ± 3.9% in the RV dysfunction group. Both CMR- derived RV SV, and EF were lower among the RV dysfunction group, (26.8 ± 15.8) ml and (35.4 ± 6.9)% respectively, with large RV systolic volume, with a highly statistically significant difference in comparison to the other group (p value = 0.000). Complications, heart block was significantly higher in patients with RV dysfunction (p value = 0.008) as it occurred in 5 (27.8%) patients. N/L ratio for predicting RV dysfunction by CMR had a cut-off value of > 7.7 with low sensitivity (38.8%) and high specificity (77.3 %). In contrast, LS for predicting RV dysfunction by CMR had high sensitivity (83.3%) and high specificity (63.6%) with p value = 0.005. Conclusion: Our results showed that RV dysfunction in inferior MI is better detected using cardiac magnetic resonance imaging. In inferior STEMI patients who underwent primary PCI, NLR has low sensitivity but high specificity for predicting RVD when measured by cardiac MRI.